2020
DOI: 10.1016/j.physa.2019.123825
|View full text |Cite
|
Sign up to set email alerts
|

Artificial neural network based modeling on unidirectional and bidirectional pedestrian flow at straight corridors

Abstract: Pedestrian modeling is a good way to predict pedestrian movement and thus can be used for controlling pedestrian crowds and guiding evacuations in emergencies. In this paper, we propose a pedestrian movement model based on artificial neural network. In the model, the pedestrian velocity vectors are predicted with two sub models, Semicircular Forward Space Based submodel (SFSB-submodel) and Rectangular Forward Space Based submodel (RFSB-submodel), respectively. Both unidirectional and bidirectional pedestrian f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Artificial neural networks have been widely used for the black-box modeling of the physical and biological systems and they have been implemented in the model-based prediction problems (Chen et al, 2020;Zhao et al, 2020). Due to higher level of complexity and chaotic dynamics, biological system modeling benefits from highly nonlinear function approximation skills of the artificial neural networks.…”
Section: A Comparison Of Training Algorithms From Shallow To Deep Tra...mentioning
confidence: 99%
“…Artificial neural networks have been widely used for the black-box modeling of the physical and biological systems and they have been implemented in the model-based prediction problems (Chen et al, 2020;Zhao et al, 2020). Due to higher level of complexity and chaotic dynamics, biological system modeling benefits from highly nonlinear function approximation skills of the artificial neural networks.…”
Section: A Comparison Of Training Algorithms From Shallow To Deep Tra...mentioning
confidence: 99%
“…In previous works, trajectory position [15] and speed in the horizontal and vertical directions [13,20] of a pedestrian at the next time step are usually chosen as the outputs. In the study of Zhao et al [21], two submodels were developed to learn the magnitude and direction of pedestrian movement velocity, respectively. Inspired by this, two submodels are proposed to predict the velocity displacement and velocity direction angle of a pedestrian at each time step, respectively.…”
Section: Development Of Ann-based Pedestrian Movement Behavior Modelmentioning
confidence: 99%
“…If unnecessary more neurons are present in the network, then "overfitting" may occur [22]. Followed by the "rules of thumb" used in the study of Zhao et al [21], the number of neurons in the hidden layer is estimated by the following equation:…”
Section: Velocity Displacement Submodel (Vdsm)mentioning
confidence: 99%
See 1 more Smart Citation
“…Congestion formation can vary widely in different architectural and geometrical contexts (Shi et al 2018 ). Many studies have identified the effects of straight corridors on the pedestrian flow (Ren et al 2019 ; Zhao et al 2020 ; Zhang et al 2011 ; Jin et al 2021 ; Heliövaara et al 2012 ). However, angled corridors exist in most walkways in public places.…”
Section: Introductionmentioning
confidence: 99%